Cost Behavior At The RBS Hotel During The COVID-19 Pandemic - Krisnadewi, Komang Ayu; Ardiana, Putu Agus; Yuristianti, Ni Putu Sri; Pratiwi, Ni Putu Adelia Maya (E-Jurnal Akuntansi; Vol 33 No 9 (2023), 2023)
This research explores into the comprehensive examination of resource management strategies employed by hotel managers, with a specific focus on committed resources and their impact on cost behavior. This study aims to determine the cost behavior of The RBS Hotel during the the COVID-19 pandemic. This study employs a qualitative descriptive research design, and utilizing interview and observation methodologies. The findings of the study indicate that managers implemented diverse tactics to facilitate cost changes, which subsequently influenced the cost behavior of hotels. The onset of the COVID-19 pandemic resulted in a shift in the behavior of hotel costs during its initial year. There has been a decrease in both employee salaries and routine maintenance costs. The non-routine maintenance tasks experienced an upward trend during the pandemic. All three exhibit characteristics of semi-fixed cost behavior. The costs associated with room facilities are subject to variation, but with a downward trend. This study makes theoretical contributions to the fields of cost behavior theory and upper echelon theory. Keywords: Cost; Cost behaviour; Covid-19; Hotel